Hakikat Ilmu Pengetahuan dalam Perspektif Filsafat Pendidikan Islam - Nadya Nadya; Fanny Syahfitri; Ilma Husnul Sabila; Widiya Widiya (FKIP, Universitas Palangka Raya, 2024)
Muslim thinkers often express the latest scientific ideas. All in all, it is done amidst a fast-paced and technologically advanced environment. The problem faced is the assumption that if Muslims can really adapt and absorb knowledge, they will advance, be able to catch up with, and match Westerners. In addition, there is an assumption that because knowledge that comes from Western nations is seen as a discussion table that divides general knowledge (Western) and religion (Eastern) it is a global challenge to science from the perspective of the philosophy of Islamic education. The purpose of this study was to find out how the nature of knowledge in the perspective of Islamic education philosophy is able to solve the problems of Islamic education so that it is able to provide clear direction and goals for implementing Islamic education using the library method. The results of the research are several sources obtained from science, namely empirical, rationalism (reason), intuitionism (intuition) and revelation. The instruments of knowledge used to gain knowledge are the senses and ratios. Then the nature of science in the perspective of the philosophy of Islamic education must be able to solve the problems of Islamic education so that it is then able to provide clear directions and goals for implementing Islamic education by implementing several aspects, namely institutional aspects, curriculum aspects, and educational aspects.